Deferred Cooling System - El Bedaiwy, Maha Farouk (AUC Knowledge Fountain, 2019)
The thesis is concerned with the development of a system for dissipating heat from a thermodynamic cycle operating in environments where fresh water is scare and ambient temperatures are high, therefore evaporative cooling is not an option whereas ambient temperatures are too high most of the day for adequate air cooling. An example of this is solar driven vapor compression cycles in desert climates. The proposed system exploits the substantially cooler night time ambient temperatures and the highly effective net radiation exchange with night sky. Since solar driven equipment require to operate during daytime when solar energy is available and hence their cycle heat is being rejected during day time hours when ambient temperatures are high, and the environment is hostile to cooling , the proposed system resorts to deferred cooling with the aid of thermal storage which can be in the form of sensible heat and water storage , however this water need not be potable and is re-usable. The thesis presents the details of implementation of the proposed system and mathematical model which can be used in its simulation and design. An experimental rig was purposely designed and built from which valuable measurements were obtained and used to demonstrate the application of the concept. Comparison between the model prediction and measurement revealed further important results. Theoretical investigation was also conducted using the proposed model to explore the system response and behavior under various weather and loading conditions. The model acts as a tool to evaluate any site’s suitability for the Deferred Cooling System (DCS) or possibly any other similar system employing radiative cooling. The results of those investigations revealed that the system is only recommended to be used under the right weather condition, in those conditions it is highly effective and efficient; indeed, it was adopted for the very hostile environment of Shallatin, Upper Egypt (23.1 °N latitude , 35.56 °E longitude ) , for a solar driven ice production project for fish preservation and proved to be quite successful.